DIFFUSE INTERSTELLAR BAND 6202 ˚ A AS AN INDICATOR OF ORGANIC MATTER IN COSMOS: CEPHEID SPECTRA - Andrievsky, S M.; Shereta, A.; Khrapaty, S. V,; Korotin, S. A.; Kovtyukh, V. V.; Kashuba, V. I. (Одеські астрономічні публікації, 2019)
We have described the method of investigation of the diffuse interstellar band (DIB) at 6202 ˚ A. This DIB is seen in the spectra of cepheid stars, and it is blended with two stellar lines of Ce II (6201.773 ˚ A) and Ni I (6204.6 ˚ A). After removal of the blending lines of ionized cerium and neutral nickel, we can determine the equivalent widths (EW) of the DIB. This procedure can be applied for the sample of cepheids (with well known distances), which enables one to construct the map of the organic matter distribution in the Galactic disc and use these values to investigate the E(B–V)–DIB EW relation. The relation found from Cepheids matches that found in B stars. This relation can help to find the reddening for newly discovered Cepheids without extensive photo- metric data, and thus determine their distances. The relation between E(B–V) and the DIB EW does not yield precise reddening values. It is not a substitute for better photometric or spectroscopic methods. At best, it is indicative, but it provides some information that may not be otherwise available.